PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DI KABUPATEN BULUNGAN - Dhinar Ika Shintyasari; Syamsuddin Bidol; Dinar Dinar (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the influence of competence and work environment on the performance of State Civil Apparatus (ASN) at the Population and Civil Registration Office of Bulungan Regency. The study employed a quantitative research approach using a survey method. The study population consisted of 47 Civil Servants (Aparatur Sipil Negara/ASN); therefore, the entire population was included as the research sample using a saturated sampling (census) technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics version 29. Prior to hypothesis testing, validity, reliability, and classical assumption tests were conducted to ensure the suitability of the research model. The results indicated that competence has a positive and significant effect on the performance of Civil Servants (ASN). The work environment also has a positive and significant effect on ASN performance. Simultaneously, competence and the work environment have a positive and significant effect on ASN performance. These findings demonstrate that competence is the most dominant factor in improving ASN performance, while the work environment serves as a supporting factor that enhances the effectiveness of task implementation. Therefore, continuous competence development, supported by a conducive work environment, is an essential strategy for improving ASN performance and the quality of public services.